Relationship Between Self Regulation with Self-Esteem of Early Childhood in Kindergarten Islamic Integrated Bina Amal Semarang City - Nurbety, Eka; Pranoto, Yuli Kurniawati Sugiyo (BELIA: Early Childhood Education Papers, 2018)
Kindergarten Islam Integrated Bina Amal Semarang is a one of the formal institutions for early childhood education. Early childhood Education has an important role to shape the personality of a child. Self-regulation and self-esteem is a one aspect of personality which is very important and affect the human behavior to adjust to the environment, because a high self-regulation and self-esteem owned by a child can affect attitudes, behaviors and various other aspects of the child. The problem in this research that there is a relationship between self-regulation with self-esteem of young children. This study has purpose to determine the relationship between self-regulation with the self-esteem of early childhood in kindergarten Islamic Integrated Bina Amal Semarang City. This study uses quantitative research correlational nature using two scales, namely Self Regulation Scale and Self-Esteem Scale of Early Childhood. The population in this study is all students of TK B who attend school in Islamic Kindergarten Integrated Bina Amal Semarang with sampling technicue that is quota sampling with amount of 36 sample research. Method of data analysis in this study using product moment correlation analysis. Based on the results of the study, shows that self regulation has a significant relationship with the self-esteem of early childhood. This is shown from the probability value (sig 2 tailed) of 0.000 < 0.05. Significant value of both variables is lower than 0.05 which implies that there is a relationship between self-regulation with the self-esteem of early childhood. The value of correlation coefficient of both variables is 0.973. Based on the interpretation of correlation coefficient of 0.800-1.00 including strong or high, it shows that the relationship between self-regulation and early child self-esteem has strong strength. The direction of the relationship between the two variables are positive. The higher the self-regulation a child has higher the self-esteem. Conversely, the lower the child’s self-regulation, the lower the child’s self-esteem.